THE DEVELOPMENT STRATEGY OF SAUMLAKI ISLAND MARINE DEFENCE AREA - Mukhlis Mukhlis; Nordi Nordi; Anton Nugroho; Okol Sri Suharyo (JOURNAL ASRO, 2021)
Saumlaki Island is the capital of the Tanimbar Islands Regency. Geographically, it is located at coordinates 1250 45'-1330 East Longitude and 60–80 30' South Latitude with an area of 5,936 km2. Saumlaki Island has a very strategic value because it is directly adjacent to Australia, so it is very vulnerable to border problems, smuggling and illegal fishing. The strategy for developing the empowerment of the marine defence area of Saumlaki Island using the SWOT and Borda methods by considering aspects of the military, social, security, political, economic, human resources, natural resources, and geography. The stages carried out is identification and evaluation of factors, strategy selection with SWOT quadrant matrix followed by SWOT and Borda matrices. The results showed that the strategy for developing the empowerment of the marine defence area of Saumlaki Island that was chosen was the Stability Strategy which is a strategy by maximizing the improvement of weakness factors (Weaknesses) to take advantage of opportunities (Opportunities). Keywords: Saumlaki Island, SWOT Method and Borda